Measuring the dynamic wind load acting on standing trees in the field without destroying them - Satoru Suzuki; Ayana Miyashita (PLoS ONE, 2025)
Wind loads are a factor in tree growth, tree architecture, and the occurrence of disasters and forest disturbances, e.g., tree falls. To understand forest ecosystems and manage forests effectively, it is necessary to understand the relationship between wind loads and trees. However, wind speed and direction always vary, which makes it difficult to measure wind loads acting on trees dynamically. We have proposed a method to accurately measure the dynamic wind load (Lw), the centroid of the dynamic wind load distribution (CL), and the dynamic wind load direction (DL) using multiple strain gauges attached to a trunk. The advantage of this method is that it can quantify the moment by separating it into Lw and CL. However, this method was only validated in a laboratory conditions by applying static loads to a cylinder pole and a small sapling. If this method can be applied to forest environments, it should provide meaningful results in areas such as forest ecology and forest conservation. Thus, in this study, the accuracy of measurement of these values was investigated under natural wind conditions to validate the feasibility of using the proposed method in a real-world field environment. At relatively higher wind speed, the accuracy of Lw was less than 10% of the systematic errors and the mean absolute percentage error (MAPE), the accuracy of CL was less than 7.7% of the MAPE, and the accuracy of DL was 12.3° of the mean absolute error (MAE). The influences of wind turbulence, the deformation of tree crown were also investigated. The results show that fluctuations in wind speed, wind direction, and the deformation have little effect on the accuracy of the values. The method employed in this study had sufficient characteristics to measure taller standing trees than the current sample in terms of sampling frequency. Thus, the method employed in this study can be widely used to measure dynamic Lw, CL, and DL of standing trees with the above accuracy in real-world field conditions.